Molecular and morphological characterization of new promising black pepper (Piper nigrum L.) lines - Sasikumar, M Sreedevi, S Syamkumar, B (Journal of Spices and Aromatic Crops, 2005)
Seven high yielding, new, promising lines of black pepper (Piper nigrum) were characterized using molecular markers (randomly amplified polymorphic DNA) and morphological features. Out of the 14 random decatner primers studied, 9 could generate unique bands in 6 lines. Maximum unique bands of the primers were observed in the line OPKrn followed by HP-1411 and HP-105. HP-780 could not be discriminated by any of the primers. Sixteen unique bands were prod uced by the nine primers making an average of 1.7 bands per primer. The lines OPKm, HP-1411 and HP-105 exhibited distinct morphological features also.